Prevalence and predictors of lower urinary tract symptoms in Solomon Islander adult men. (September 2021) - Lui, Paraniala Silas C; Dorji, Nidup
Background: Despite growing interest in the prevention of lower urinary tract symptoms (LUTS) globally and in the Asia-Pacific region, population-based evidence is limited in the smaller Pacific Island countries such as in the Solomon Islands. This study aimed to investigate the prevalence and describe the risk factors associated with moderate to severe LUTS among Solomon Islander men. Methods: A cross-sectional survey was conducted among 400 men aged ⩾18 years living in Honiara, Solomon Islands. LUTS were assessed using the International Prostate Symptom Score (IPSS). The association between moderate to severe LUTS and sociodemographic, health conditions and health-related factors were estimated using logistic regression adjusted for age. Results: Overall, 13.8% reported moderate LUTS, and 0.8% reported severe LUTS. Frequent night-time urination was the most commonly reported LUTS. The adjusted odds of moderate to severe LUTS decreased with increasing level of education. The odds increased among men reporting elevated psychological distress, increased stressful events in the past 12 months and depression. Conclusions: About one in six Solomon Islander men experience moderate to severe LUTS, having a negative impact on their mental health and general well-being.